1998
DOI: 10.1016/s0893-133x(97)00092-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Modulation of Dopamine Measured in Vivo with Positron Emission Tomography (PET) and 11C-Raclopride in Normal Human Subjects

Abstract: Subanesthetic doses of the noncompetitive N-methyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…However, Adams et al (2002) found that ketamine did not stimulate dopamine release in non-human primates. In humans, ketamine’s effect on dopaminergic neuro-transmission is even more controversial (Aalto et al, 2005, 2002; Breier et al, 1998; Smith et al, 1998; Kegeles et al, 2002; Vernaleken et al, 2013). With regard to psychotomimetic effects, (Sos et al, 2013) BPRS subscales were not correlated with antidepressant response in depressed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, Adams et al (2002) found that ketamine did not stimulate dopamine release in non-human primates. In humans, ketamine’s effect on dopaminergic neuro-transmission is even more controversial (Aalto et al, 2005, 2002; Breier et al, 1998; Smith et al, 1998; Kegeles et al, 2002; Vernaleken et al, 2013). With regard to psychotomimetic effects, (Sos et al, 2013) BPRS subscales were not correlated with antidepressant response in depressed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine (DA) neurotransmission and neural circuits involving the dorsolateral prefrontal cortex (DLPFC) and the striatum have been most consistently implicated in processing speed, psychomotor and executive functioning. Ketamine has been observed to modulate DA transmission (Krystal et al 2005; Smith et al 1998; Vollenweider et al 2000), although the extent to which this is related to its antidepressant activity is not known. Beyond DA, preclinical studies have implicated alterations in neuroplasticity via several mechanisms – including modulation of brain-derived neurotrophic factor (BDNF) – as critical to ketamine’s antidepressant action (Autry et al 2011; Duman 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is well known for neurological applications and many reports describe the effect of anaesthetics, mostly barbiturates, on brain function [4], [5], [6]. However, less is published on the general impact of anaesthesia on extracerebral metabolism, especially in nuclear medicine applications.…”
Section: Introductionmentioning
confidence: 99%